The results of endoscopic tratment in esophageal variceal bleeding - Ülkü SARITAŞ,; Emin ALTIPARMAK,; Azmi SERİN,; Uğur YILMAZ,; Çağlar BAYSAL,; Burhan ŞAHİN, (Turkish Journal of Gastroenterology, 2019)
-